European net-winged beetles of the Pyropterus clade, with the description of Gomezzuritus gen. nov. (Coleoptera: Lycidae) - Kazantsev, Sergey V.; Motyka, Michal; Bocak, Ladislav (European Journal of Taxonomy, 2023)
We simultaneously considered morphology and molecular phylogeny to modify the generic classification of the ‘pyropterine clade’ (Lycidae, Erotinae, Dictyopterini). To place species previously included in Benibotarus Kôno, 1932 in reciprocally monophyletic genera, we propose Gomezzuritus gen. nov. with the type-species Dictyopterus alternatus Fairmaire, 1856. Further, we transfer Gomezzuritus alternatus (Fairmaire, 1856) comb. nov., G. longicornis (Reiche, 1878) comb. nov., and G. rubripes (Pic, 1897) comb. nov. from Benibotarus to Gomezzuritus gen. nov. The pyropterine clade contains five genera in the Palaearctic region: Pyropterus Mulsant, 1838, Gomezzuritus gen. nov., Helcophorus Fairmaire, 1891, Greenarus Kazantsev, 1995, and Benibotarus Kôno, 1932. The arrangement of longitudinal elytral costae proved misleading for consideration of relationships. Two genera in distant positions share only four primary costae (Pyropterus and Helcophorus), and three similarly distant genera share the shortened primary costa 3, resulting in three primary and four secondary longitudinal costae (Gomezzuritus, Greenarus, and Benibotarus). The larva of Gomezzuritus alternatus is described in detail, and it is compared with the larvae of other Dictyopterini, including the presumed larva of G. longicornis.